2016
DOI: 10.17221/8765-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monosodium l-glutamate administration on the reproduction and serum biochemistry of adult male rabbits

Abstract: ABSTRACT:In this study the effects of monosodium l-glutamate (MSG) administration on the reproductive parameters and serum biochemistry of male rabbits were investigated. Sixteen mature male New Zealand mixed-breed of rabbits (Oryctolagus species) weighing 1.1-1.65 kg were used for this study. They were randomised into four groups of four rabbits each. Group A which served as the untreated control, received only distilled water while Groups B, C and D which were the treated groups, received 0.25 g/kg, 0.5 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The degenerative changes in germ and somatic cells of ST may be arisen from the interaction of MSG with proteins and enzymes interfering with the antioxidant defense mechanism leading to accumulation of free radicals which in turn induces inflammatory reaction and mitochondrial damage 88 . On the contrary, other studies did not find any histological lesions in the testicular tissue of animals received MSG 10 , 89 due to intake of low doses.…”
Section: Discussionmentioning
confidence: 74%
“…The degenerative changes in germ and somatic cells of ST may be arisen from the interaction of MSG with proteins and enzymes interfering with the antioxidant defense mechanism leading to accumulation of free radicals which in turn induces inflammatory reaction and mitochondrial damage 88 . On the contrary, other studies did not find any histological lesions in the testicular tissue of animals received MSG 10 , 89 due to intake of low doses.…”
Section: Discussionmentioning
confidence: 74%
“…[ 38 ] and Okoye et al . [ 39 ] did not find any histological lesions in the testicular tissue of animals receiving MSG.…”
Section: Discussionmentioning
confidence: 98%
“…There are various studies which suggested that thymocytes, lymphocytes, and thymic stromal cells also possess the receptors for glutamate ( Pavlovic et al, 2006 ). Further, it is reported that MSG comprises two isomers, i.e., L-glutamate and D-glutamate enantiomers, but only L-glutamate enantiomer is responsible for enhancing the flavor ( Okoye et al, 2016 ). Processed MSG comprises 99.6% L-glutamate form which is a greater percentage of L-glutamate than that observed in the free glutamate ions of naturally occurring foods ( Halpern, 2000 ).…”
Section: Introductionmentioning
confidence: 99%